Prevalence of abnormal kidney function in a rural population of Benin and associated risk factors - Gbaguidi, Gwladys; HOUINATO, Dismand (My University, 2021)
Background The global burden of kidney disease has increased in recent years worldwide. Risk factors for kidney disease are common in Africa, but data on their prevalence are lacking. This study aims to determine the prevalence of abnormal kidney function and associated factors among participants included in the TAnve HEalth Study (TAHES) cohort in Benin. Methods This was a cross-sectional study nested within the TAHES cohort. It was carried out in 2019, among TAHES participants aged 25 years and above, living in Tanvè and Dékanmè, two villages located in southwestern Benin. Data on risk factors were collected using the World Health Organization’s STEPS questionnaire. Anthropometric measurements and capillary creatinine measurements were performed. Abnormal kidney function was defined as a low glomerular filtration rate (< 60 mL/min/1.73 m2). Results Creatinine was measured among 1360 out of the 1583 participants in the cohort in 2019. The median age was 39 [32–53]. The prevalence of abnormal kidney function was 16.10%; 95%CI = [14.15–18.05]. The results of the multivariate logistic regression showed that the probability of abnormal kidney function increased significantly with age (adjusted OR (aOR) = 2.75; 95%CI = [1.83–4.14]), female gender (aOR = 2; 95%CI = [1.37–2.91]), hypertension (aOR = 1.54; 95%CI = [1.12–2.13]), high body mass index (aOR = 1, 56; 95%CI = [1.12–2.17]) and hyperglycemia (aOR = 2.86; 95%CI = [1.68–4.88]). Conclusion The prevalence of abnormal kidney function was high. These data should guide national authorities and help to raise community awareness of the benefits of early detection of this condition.
Keywords: Abnormal kidney function; Prevalence; Associated factors; Rural area; Benin